The Risk of Developing of Malnutrition and the Principles of Correction of Nutritional Status Disorders in Children with Cystic Fibrosis - Elena I. Kleshchenko; Elena V. Shimchenko; Aleksander F. Komarov; Valeria E. Kharchenko (Педиатрическая фармакология)
Cystic fibrosis is a severe hereditary disease with polysystemic manifestations and progressive course. Malnutrition in cystic fibrosis occurs as a result of exocrine insufficiency of the pancreas, an increase in energy losses in chronic inflammation in the bronchopulmonary system, manifested by increased stress on the respiratory system. The presented literature review highlights the modern principles of prevention and correction of malnutrition in children with cystic fibrosis, identifies the most promising methods for further development that correct nutritional status disorders. The review has shown that an active approach to nutrition at any age, the use of aggressive methods of nutritional support against the background of enzyme replacement therapy, timely and adequate therapy of respiratory tract pathology lead to an improvement in the indicators of nutritional status in cystic fibrosis. The most promising is the further development of targeted therapy, which allows, as a result of exposure to the etiopathogenetic mechanisms of the disease, to reduce the frequency and severity of bronchopulmonary exacerbations, partially restore the exocrine function of the pancreas, which is manifested in patients with cystic fibrosis by an increase in body weight and mass-growth index.